PERCEPÇÃO AMBIENTAL NA GESTÃO DE ESPAÇOS PÚBLICOS: O CASO DA COHAB FERNANDO FERRARI, SANTA MARIA, RS - Szymczak, Denise Andréia; Brun, Flávia Gizele Konig; Kleinpaul, Isabel Sandra; Marafiga, Joseane Savian; Krampe, Adriane Lisboa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704993 Arboreous public spaces are of great importance for the population life quality. With the objectiveof reflecting about the environmental perception and the administration of these spaces, it wascarried out a study of case on the Conjunto Habitacional (Cohab) Fernando Ferrari Square on theresidents as well. A questionnaire with open questions was applied in order to approach the mainuses of the place and the interviewees' possible improvements. The majority of them didn't makeany use of the place (53,19%), the others used mainly for the children's recreation and pot luckyparties. As a consequence of the lack of safety (17,02%) the vandalism was shown beyond as themain agent of the public patrimony pillaging that provokes fear among the users, mainly children.Among the improvements suggested by the interviewees there are improvements of the toys infrastructure (48,93%) and the safety of the Square. For a better administration of the publicspaces, the Environmental Education can act as an instrument to change the residents attitudesrelated to the atmosphere of that place, by reinforcing a previous existent perception so thatforming conscious and actives citizens in the community.